-cos(pi)/pi = 1/pi
So your equation becomes
0 = 1/pi + c
c = -1/pi
y = -cos(x)/x - 1/pi
(edit)
The above corresponds to a previous error in calculation, but I have left it so the following posts don't appear unmotivated
xy'+y= sinx IVP is y(pi)=0
My attempt:
y' +y/x = sinx/x
Finding the I.F
e^$1/x * dx = e^lnx
I.F is x
Muliply all the equation by x
xy' + y = sinx
Restate the equation
(x*y)' = sinx
xy = -cosx + c
y = -cosx / x + c
I think i have done right so far, but I dont know how to to evaluate it with the
values look:
0 = - cos pi / pi + c ??? what How do i evaluate that?
-cos(pi)/pi = 1/pi
So your equation becomes
0 = 1/pi + c
c = -1/pi
y = -cos(x)/x - 1/pi
(edit)
The above corresponds to a previous error in calculation, but I have left it so the following posts don't appear unmotivated